A study on customer satisfaction at Mydin Wholesale Emporium Jalan Masjid India / Faridah Ahmad - Ahmad, Faridah (1998)
Retailing in Malaysia has been growing tremendously over the last few years. The competition among retailers are getting more fierce. The global marketplace continues to be very competitive. Businesses have been challenged to increase their levels of quality, convenience and improve their pricing strategies. One of the most important objectives in the marketplace today is providing total customer satisfaction. Customer expressed their satisfaction based on their experiences and expectations. The subjectivity of customer satisfaction has created a challenged to businesses. In this study, it was determined that customers are satisfied when they are courteously treated, when the products sold are within their affordable budget, feels comfortable and save within the shopping environment as well as easily accessible to the location. In the economie slowdown, customers are getting smarter in planning their purchasing. They will look for a better place to shop where the price is cheap regardless the quality of the products as compared to other competitors. To customers that perceived price as their top consideration, this had driven them to their satisfaction